Unfinished Christians: Ritual Objects and Silent Subjects in Late Antiquity. - Bailey, Lisa Kaaren (History of Religions, 2025)
The main focus of the text is "Unfinished Christians: Ritual Objects and Silent Subjects in Late Antiquity," a book by Georgia Frank that explores the emotional and sensory experiences of ordinary Christians in late antiquity through the lens of ritual objects and practices. Frank argues that these objects reflect the humanity and agency of the people who created and used them, emphasizing the concept of "crafting" as an ongoing process rather than a completed act. The book examines various aspects of Christian rituals, including baptism, processions, and liturgical experiences, while also addressing the emotional complexities involved, including the darker sides of emotional manipulation. Although the analysis raises questions about the definition of "ordinary Christians" and the effectiveness of rituals, it is praised for its compassionate and insightful exploration of the lived experiences of individuals in this historical context.